2010
DOI: 10.1111/j.1365-2788.2010.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception and frontal lobe in intellectual disabilities: a study with evoked potentials and neuropsychology

Abstract: The systematic correlations, produced by the target stimulus in perceptual abilities tasks, with the N1a (frontal) and not with N1b (posterior), suggest that the visual perception process involves frontal participation. These correlations support the idea that the N1a and N1b are not equivalent. The relationship between frontal functions and early stages of visual perception is revised and discussed, as well as the frontal contribution with the neuropsychological tests used. A possible relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
(166 reference statements)
0
6
0
Order By: Relevance
“…These studies support the “early selection” theories of visual-spatial attention (Bashinski and Bacharach, 1980; Johnston and Dark, 1986; Downing, 1988; Hillyard and Anllo-Vento, 1998); however a different role of the P1 and N1 components should be considered (Luck et al, 1990). The P1 component enhancement represents facilitation at the early sensory processing level for items presented at attended location (Di Russo et al, 2003), while the N1 component is associated with the discrimination processes within the focus of attention (Luck et al, 1990; Vogel and Luck, 2000). In addition to the modulation of the extrastriate areas, visual attention control relies on a network of cortical and subcortical regions, including the DLPFC and PPC, the anterior cingulate gyrus, and the pulvinar nucleus of the thalamus (Mesulam, 1990; Nobre et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These studies support the “early selection” theories of visual-spatial attention (Bashinski and Bacharach, 1980; Johnston and Dark, 1986; Downing, 1988; Hillyard and Anllo-Vento, 1998); however a different role of the P1 and N1 components should be considered (Luck et al, 1990). The P1 component enhancement represents facilitation at the early sensory processing level for items presented at attended location (Di Russo et al, 2003), while the N1 component is associated with the discrimination processes within the focus of attention (Luck et al, 1990; Vogel and Luck, 2000). In addition to the modulation of the extrastriate areas, visual attention control relies on a network of cortical and subcortical regions, including the DLPFC and PPC, the anterior cingulate gyrus, and the pulvinar nucleus of the thalamus (Mesulam, 1990; Nobre et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…One example of this is a VP training program intended to improve VP and attentional ability through training perceptual discrimination between figure and ground. A study found that VP processing involves the frontal lobes in individuals with IDs (Muñoz-Ruata, Caro-Martínez, Pérez, & Borja, 2010). Consequently, VP training is expected to enhance frontal lobe function.…”
Section: Introductionmentioning
confidence: 99%
“…Since a working memory task was not conducted in this region during cortical stimulation due to time constraints, a lack of function using visual naming tasks was somewhat expected. Overall decreases in the visual Working Memory Index and the Perceptual Reasoning Index lead us to speculate that this area was likely destabilized by cortical dysgenesis [28,29] and that this area did not reorganize a second time following the second surgical resection.…”
Section: Results and Discussion—case Reportmentioning
confidence: 99%